2004
DOI: 10.1111/j.1523-1755.2004.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone prevents early renal injury in streptozotocin-induced diabetic rats

Abstract: Streptozotocin-induced renal fibrosis, PAI-1 expression, TGF-beta1 expression, and macrophage infiltration occur via mineralocorticoid receptor, and spironolactone ameliorates renal fibrosis presumably via the inhibition of macrophage infiltration, PAI-1 expression, and TGF-beta1 expression in streptozotocin-induced early diabetic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
118
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 56 publications
(54 reference statements)
22
118
0
7
Order By: Relevance
“…43,44 Results obtained in CCD from rats under low-Na diet and evidence obtained in cultured nonclassical aldosterone-responsive proximal tubular cells 45 or glomerular mesangial cells 12 strongly suggest that aldosterone may induce or enhance tubulointerstitial and glomerular BASIC RESEARCH www.jasn.org inflammation and fibrosis via NF-B activation. Along with our results, these observations provide a rationale for the beneficial effects of administration of MR antagonists in both experimental [45][46][47] and human chronic kidney disease. 48 Independent from this suspected role in chronic renal disease progression, activation of NF-B by aldosterone may play a role in controlled sodium and water reabsorption by the CD.…”
Section: Discussionsupporting
confidence: 77%
“…43,44 Results obtained in CCD from rats under low-Na diet and evidence obtained in cultured nonclassical aldosterone-responsive proximal tubular cells 45 or glomerular mesangial cells 12 strongly suggest that aldosterone may induce or enhance tubulointerstitial and glomerular BASIC RESEARCH www.jasn.org inflammation and fibrosis via NF-B activation. Along with our results, these observations provide a rationale for the beneficial effects of administration of MR antagonists in both experimental [45][46][47] and human chronic kidney disease. 48 Independent from this suspected role in chronic renal disease progression, activation of NF-B by aldosterone may play a role in controlled sodium and water reabsorption by the CD.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, the serum creatinine, blood urea nitrogen and proteinuria were noted to be significantly increased in STZ-induced diabetic rats as compared to normal rats. The increased ratio of kidney weight/body weight may contribute to renal hypertrophy which leads to diabetic nephropathy progression (Fujisawa et al, 2004). These words are supported by our study that there is significant increase in the ratio of kidney weight/body weight in diabetic rats.…”
Section: Discussionsupporting
confidence: 71%
“…112 The beneficial effects of aldosterone blockade on diabetic nephropathy seem to be independent of the blood pressure reduction 112 and RAAS blockade on diabetic nephropathy. 113 The mechanism by which an aldosterone blocker improves diabetic nephropathy is not totally clear; however, antiinflammatory 114,115 and/or anti-oxidant 116 mechanisms have been suggested as possibilities. To this end, it has been shown that the induction of diabetes in rats leads to a reduction in glucose-6-phosphate dehydrogenase (G6PD) and oxidative stress.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 99%